2019
DOI: 10.1007/s40201-018-00327-w
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical composition of PM10 and its effect on in vitro hemolysis of human red blood cells (RBCs): a comparison study during dust storm and inversion

Abstract: Purpose This study aimed to investigate chemical composition of PM 10 (particulate matter with aerodynamic diameter ≤ 10 μm) during dust storm and inversion in Tehran and hemolysis effects. Methods PM 10 was sampled in Tehran, Iran, during dust storm and inversion conditions. Water soluble ions (F¯, Cl¯, NO 2¯, NO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…PM 2.5 in Beijing during a pollution episode had a TD 10 value ranging from 1803.27 µg/mL to 3224.48 µg/mL, with an average of 2432.48 µg/mL. The TD 10 of PM 2.5 in this study was significantly higher than that in a previous study in Tehran, which concluded that the mean value TD 10 of PM 10 during a dust storm was 150 µg/mL and the mean value TD 10 of PM 10 during a weather inversion was 220 µg/mL [26]. This indicated that thanks to the implementation of a series of pollution prevention and control measures from 2013 to 2017, the source structure of PM 2.5 in Beijing has changed, and its chemical composition has also changed, resulting in a decrease in toxicity.…”
Section: Dose-response Relationship Between Hemolysis and Pm 25contrasting
confidence: 72%
See 1 more Smart Citation
“…PM 2.5 in Beijing during a pollution episode had a TD 10 value ranging from 1803.27 µg/mL to 3224.48 µg/mL, with an average of 2432.48 µg/mL. The TD 10 of PM 2.5 in this study was significantly higher than that in a previous study in Tehran, which concluded that the mean value TD 10 of PM 10 during a dust storm was 150 µg/mL and the mean value TD 10 of PM 10 during a weather inversion was 220 µg/mL [26]. This indicated that thanks to the implementation of a series of pollution prevention and control measures from 2013 to 2017, the source structure of PM 2.5 in Beijing has changed, and its chemical composition has also changed, resulting in a decrease in toxicity.…”
Section: Dose-response Relationship Between Hemolysis and Pm 25contrasting
confidence: 72%
“…Many methods have been used to assess the toxicity of particles, incorporating both in vivo [ 20 , 21 ] and in vitro methods [ 22 , 23 , 24 ]. Due to complicated experimental processes, long test periods, and high costs of in vivo methods, researchers are now utilizing in vitro protocols for rapid toxicological analysis of atmospheric PM, such as the hemolysis assay [ 25 , 26 ], plasmid scission assay (PSA) [ 27 ], and apoptosis assay [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rats that were experimentally stressed using electric shock had lower RBC and hemoglobin in comparison with a non-stressed control group (Wei et al, 2008). Further, PM from dust and from coal-burning environments have increased hemolytic effects on RBC (Faraji et al, 2019;Zhang et al, 2022). The heavy metal portion of PM, specifically, appears to play a large role in determining the severity of the hemolytic effect (Zhang et al, 2022).…”
Section: Hematology and The Acute Phase Responsementioning
confidence: 99%
“…The pollutants in the dust combined with intensified desertification in China are resulting in more and longer DS events [ 12 , 13 ]. Particulate matter (PM) concentration levels also increase due to DS [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%